Risiko for bias i retspsykiatriske vurderinger - Susanne Bengtson; Pia Lykke Hjortebjerg (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract To reach better-informed decisions about psycho-legal issues, courts in Denmark and other countries request psychiatric and psychological expertise opinions on emotional, behavioral, and/or cognitive functioning of charged individuals and on court sentencing for convicts. The process of professional decision-making has, however, for decades been recognized as vulnerable to becoming biased. Biases are a potential result of humans’ applying  cognitive short-cuts ( heuristics) to ensure fast and effective decision-making. While bias in forensic psychiatry has been examined internationally, this subject has been issued only scarcely in Denmark. This paper aims to introduce to theoretical basics and empirical findings on bias, cognitive heuristics, and debiasing strategies broadly and specifically to forensic psychiatry. The objective is to inform and improve professional practice within forensic psychiatry.